Cor Triatriatum in an Adult - Hirachan, Anish; Prajapati, Dipanker; Roka, Madhu; Dhungana, Murari; Sharma, Deewakar (Nepalese Heart Journal, 2017)
A 29 year old female patient presented to the cardiology OPD with history of progressive breathlessness of NYHA class II and palpitation of 1 year duration. Under evaluation, she underwent 2D transthoracic echocardiography that revealed an extra septum that subdivided the left atrium into proximal and distal chambers. The diagnosis of cor triatriatum was hence made and was referred to surgical team for corrective surgery. The communication between proximal and distal chamber was provided by large fenestration in the fibromuscular membrane. Nepalese Heart Journal 2017; 14(1): 33-34